2005
DOI: 10.1007/s11745-005-1424-y
|View full text |Cite
|
Sign up to set email alerts
|

Unusual minor nonmethylene‐interrupted di‐, tri‐, and tetraenoic fatty acids in limpet gonads

Abstract: Unusual minor nonmethylene-interrupted (NMI) FA have been identified in the lipids of gonads from the limpets Cellana grata and Collisella dorsuosa by using GC-MS of the combination of their 4,4-dimethyloxazoline derivatives and picolinyl esters. Among 23 NMI unsaturated FA from C18 to C22 and C24 identified in this study, 5,11-nonadecadienoic (5,11-19:2), 7,1 6-heneicosadienoic (7,16-21:2), 9,15-tetracosadienoic (9,15-24:2), 5,9,15-docosatrienoic (5,9,15-22:3), and 5,9,15-tetracosatrienoic (5,9,15-24:3) acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 17 publications
2
27
2
Order By: Relevance
“…These fatty acids are not found in the algae usually consumed by sea urchins; thus, their presence in the gonads of both sea urchins species suggests that they have been formed endogenously by 5 desaturation of their immediate precursors 20:1n-9 and 20:1n-7, as previously described by Zhukova (1991) in molluscs. The levels of NMID were reported to be higher in the female gonads of two limpet species when compared to the male gonads (Kawashima 2005). In our study, the two identiWed NMID showed also higher proportions in ovaries than in testes although diVerences were only signiWcant in A. lixula and not in P. lividus.…”
Section: Discussioncontrasting
confidence: 39%
“…These fatty acids are not found in the algae usually consumed by sea urchins; thus, their presence in the gonads of both sea urchins species suggests that they have been formed endogenously by 5 desaturation of their immediate precursors 20:1n-9 and 20:1n-7, as previously described by Zhukova (1991) in molluscs. The levels of NMID were reported to be higher in the female gonads of two limpet species when compared to the male gonads (Kawashima 2005). In our study, the two identiWed NMID showed also higher proportions in ovaries than in testes although diVerences were only signiWcant in A. lixula and not in P. lividus.…”
Section: Discussioncontrasting
confidence: 39%
“…Marked differences between male and female gonads of the two dominant limpet species, Cellana grata and Collisella dorsuosa, were also characterized by the composition and proportions of unusual NMI fatty acids, and the proportions of 16:0, 20:4n-6 and 20:5n-3 as major fatty acid components. Although the unusual long-chain C 24 unsaturated fatty acids in limpet gonads were found in only small or trace amounts, 3) detailed clarification of their positional isomers was not done in the previous study. This paper describes the occurrence of minor C 24 unsaturated fatty acids, including an unusual diene, triene, tetraene, and pentaene in female gonad lipids of C. grata, which may not have been described previously.…”
mentioning
confidence: 89%
“…[1][2][3] But their biological role and function in living organisms are not fully understood. A study of the determination of minor fatty acids might provide valuable information for comparative biochemical research on the effects of environmental factors and/or physiological conditions on fatty acid compositions in organisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations